Solubility of Bicalutamide, Megestrol Acetate, Prednisolone, Beclomethasone Dipropionate, and Clarithromycin in Subcritical Water at Different Temperatures from 383.15 to 443.15 K - Pu, Y.; Cai, F.; Wang, D.; Li, Y.; Chen, X.; Maimouna, A.; Wu, Z.; Wen, X.; Chen, J.; Foster, Neil (American Chemical Society, 2017)
© 2017 American Chemical Society. The solubility of bicalutamide, megestrol acetate, prednisolone, beclomethasone dipropionate, and clarithromycin in subcritical water (SBCW) at the temperature range from 383.15 to 443.15 K and constant pressure of 5.5 MPa were measured using a modified solvent-antisolvent method combined with SBCW technology. The chemical structures of these five kinds of solutes were stable after processed in SBCW at up to 443.15 K, which was demonstrated by Fourier transformed infrared analysis. The solubility of selected solutes increased exponentially as the temperature of the SBCW increased from 383.15 to 443.15 K. The obtained solubility data were correlated using a modified Apelblat model and the results of the predicted solubility show good agreement with the experimental value. (Graph Presented).